1933 Pixely Cotton Strike - Farm Security Administration:::Creator::::::::::::
In a Pixley Cotton Strike camp with women and children in an eating area. Pixley is a town in Tulare County, California. In 1933, Pixley was one of the towns in California involved in the San Joaquin cotton strike, a labor action by agricultural workers seeking higher wages. A violent clash between strikers and growers left two workers dead and eight wounded. Five thousand workers gathered in Tulare for the dead strikers' funerals, one of the largest agricultural demonstrations in California's history. Eight cotton growers were indicted in the violence against the workers, but were later acquitted.